2020
DOI: 10.1007/s11096-020-01049-6
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and drug therapy, what we learned

Abstract: COVID-19, the disease associated in December 2019 with the novel coronavirus SARS-CoV-2, was observed for the first time in China and then spread worldwide becoming pandemic. Currently, there is still no licensed specific antiviral treatment for the human coronavirus disease and a vaccine will not be ready soon. However, based on experience from the use of other antiviral agents to treat similar virusses, some treatment options have been tried with some efficacy. Clinical trials for future therapies are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…This is particularly true for the lab testing capacity, which has increased since the beginning of the pandemic, 29 and the list of drugs included because the therapeutic guidelines and protocols for patients with SARS-CoV-2 have extensively changed over time. 30 …”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for the lab testing capacity, which has increased since the beginning of the pandemic, 29 and the list of drugs included because the therapeutic guidelines and protocols for patients with SARS-CoV-2 have extensively changed over time. 30 …”
Section: Discussionmentioning
confidence: 99%
“…In general, the pharmacological treatment in nonhospital settings is not recommended, as well as for young, healthy patients with mild symptoms, and without comorbidities 50 . Through the clinical treatment of the COVID‐19, it has been found that neuraminidase inhibitors (such as oseltamivir, peramivir, and zanamivir) are not sufficient, as this viral enzyme is not produced by coronaviruses.…”
Section: Treatments That Are Not Recommendedmentioning
confidence: 99%
“…Although SARS‐CoV‐2 infection is associated with a cytokine storm triggered by overactivation of the immune system, the corticosteroids treatment was not initially recommended for viral pneumonia, only for patients with refractory shock or acute respiratory distress syndrome 18,49–51 . Currently, a systematic living review and network meta‐analysis with data from eight randomized trials (7184 participants) made a strong recommendation for use of corticosteroids in severe and critical COVID‐19 because there is a lower risk of death among people treated with systemic corticosteroids (moderate certainty evidence).…”
Section: Treatments That Are Not Recommendedmentioning
confidence: 99%
“…Coronavirus infection COVID-19 (abbreviation for the English COronaVIrus Disease 2019) is a potentially severe critical respiratory infection caused by the coronavirus SARS-CoV-2 (2019-nCoV) [2], a dangerous disease that can occur in the form of an acute respiratory viral infection of the lung [3].…”
Section: Introductionmentioning
confidence: 99%